Situation in Spain - Bilbao : memorandum of interviews with Santiago Aznar and Anthony Eden - Aznar, Santiago ; Eden, Anthony, Earl of Avon, 1897-1977; Citrine, Walter, 1887-1983
1937-04-20 016a-0044-001 292/946/16a/45(i)